Effect of Carbon Nanotube-Metal Hybrid Particle Exposure to Freshwater Algae Chlamydomonas reinhardtii - Worawit Intrchom (Nature Portfolio, 2018)
Abstract We demonstrate for the first time the toxicity of carbon nanotube (CNT) metal hybrids on freshwater algae. Carbon nanotube-silver (CNT-Ag) and platinum hybrids (CNT-Pt) were synthesized and exposed to Chlamydomonas reinhardtii (C. reinhardtii), and their toxicity was compared to the pure metal salts. Interactions between CNT-metal and algae were studied using electron microscopy and it was observed that while outer membrane of the algal cell was damaged as a result of Ag+ toxicity from pure Ag, the CNT-Ag only caused the distortion of the cell wall. It was also observed that the CNT-Ag particles could be internalized and enclosed in internal vesicles in the algal cells. Long-term exposure of the CNT-metals showed delay in algal growth. CNT-Ag at a concentration of 5.0 mg/L showed 90% growth inhibition and also showed a significant effect on photosynthetic yield with a 21% drop compared to the control. It was observed that pure silver was more toxic compared with CNT-Ag for both growth and photosynthesis in the 96-hour exposure. In general, CNT-Pt showed significantly less toxic effects on the algae than CNT-Ag. Based on this study, it is postulated that the CNT suppressed the release of Ag+ from CNT-Ag hybrids, thus reducing overall toxicity.